Direct estimation of depth to geological causative bodies using the half-width concept of gravity and magnetic methods - Ibim, Dagogo Franklin (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
Direct estimation of depth to geological causative bodies using half-width gravity and magnetic methods was carried out. This paper aims to estimate the vertical depth to the centre of a causative body in gravity and magnetic profiles. 3D body (sphere in case of geometrical body), and cylindrical body were considered in the estimation. The depth Z to the centre of the homogeneous sphere and cylinder from the gravity effect was estimated to be 1.305X1/2 and 0.577X1/2 respectively. The depth Z to the centre of a homogeneous sphere from the magnetic effect was estimated to be 1.5X1/2. This paper has shown that it is possible to use gravity results to determine magnetic effects for the equivalent geometrical shapes, through the use of Poisson's relations. Only 2D features in this study are generally amenable to derivation. To ensure a high degree of accuracy, I recommend among other methods the use of source parameter imaging techniques for aeromagnetic and gravity data for the estimation of causative depth in any area of interest.